Epigenome-wide skeletal muscle DNA methylation profiles at the background of distinct metabolic types and ryanodine receptor variation in pigs - Ponsuksili, Siriluck (BMC Genomics, 2019)
BACKGROUND: Epigenetic variation may result from selection for complex traits related to metabolic processes or appear in the course of adaptation to mediate responses to exogenous stressors. Moreover epigenetic marks, in particular the DNA methylation state, of specific loci are driven by genetic variation. In this sense, polymorphism with major gene effects on metabolic and cell signaling processes, like the variation of the ryanodine receptors in skeletal muscle, may affect DNA methylation. METHODS: DNA-Methylation profiles were generated applying Reduced Representation Bisulfite Sequencing (RRBS) on 17 Musculus longissimus dorsi samples. We examined DNA methylation in skeletal muscle of pig breeds differing in metabolic type, Duroc and Pietrain. We also included F2 crosses of these breeds to get a first clue to DNA methylation sites that may contribute to breed differences. Moreover, we compared DNA methylation in muscle tissue of Pietrain pigs differing in genotypes at the gene encoding the Ca2+ release channel (RYR1) that largely affects muscle physiology. RESULTS: More than 2000 differently methylated sites were found between breeds including changes in methylation profiles of METRNL, IDH3B, COMMD6, and SLC22A18, genes involved in lipid metabolism. Depending on RYR1 genotype there were 1060 differently methylated sites including some functionally related genes, such as CABP2 and EHD, which play a role in buffering free cytosolic Ca(2+) or interact with the Na(+)/Ca(2+) exchanger. CONCLUSIONS: The change in the level of methylation between the breeds is probably the result of the long-term selection process for quantitative traits involving an infinite number of genes, or it may be the result of a major gene mutation that plays an important role in muscle metabolism and triggers extensive compensatory processes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5880-1) contains supplementary material, which is available to authorized users.